Accommodative spasm with bilateral vision loss due to untreated intermittent exotropia in an adult - Shanker, V; Ganesh, S; Sethi, S (Nepalese Journal of Ophthalmology, 2012)
Background: Intermittent exotropia (IXT) is an exodeviation intermittently controlled by fusional mechanisms. Patients with IXT may present with asthenopic symptoms, blurred vision, headaches, diplopia or visual confusion and reading difficulties; especially after prolonged periods of near work. Objective: To report the presentation and management of a young adult with intractable accommodative spasm secondary to long standing intermittent exotropia. Case: The patient was found to have bilateral accommodative spasm with high pseudomyopia and severe impairment of vision. There was a tendency for recurrence with discontinuation of cycloplegics. Conclusion: A total relief of symptoms was noticed after strabismus surgery was undertaken for the exotropia. A detailed orthoptic evaluation with emphasis on recognizing accommodative spasm as an unusual presentation of IXT, could aid in appropriate diagnosis and treatment of such cases. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6552 Nepal J Ophthalmol 2012; 4 (2): 319-322